APPLICATION OF FAST WAVELET TRANSFORM FOR THE SOLUTION OF DIRECT PROBLEM OF GRAVIMETRIC PROSPECTING - Dolgal A.S. (My University, 2004)
The approximation of real distribution of physical inhomogeneities in a geological medium by a number of bodies of correct geometrical form is a necessary stage in the analytical solution of the direct problem of gravimetric prospecting. The FWT (Fast Wavelet Transform) method of optimization of the piecewise-prismatic approximation of geological objects can be successfully used for the solution of direct problems in several other geophysical methods (e.g., magnetic exploration, electric charge logging, and others). The FWT is especially efficient in combination with iteration algorithms of trial-and-error methods based on multiple solution of the direct problem related to successively refined models of the geological structure of terrains under study.